Karakteristik Pelet dari Bagian Pohon Gelam (Melaleuca cajuputi subsp. Cumingiana) dengan Persentase Perekat Tapioka yang Berbeda - Alpian, Alpian; Nuwa, Nuwa; Supriyati, Wahyu; Firdara, Eritha Kristiana; Luhan, Gimson; Yanciluk, Yanciluk; Pratama, Redi Saputra (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2025)
As fossil fuels continue to deplete, alternative energy sources need to be explored. Wood pellets process sawdust into fuel. This study examines wood pellets made from Gelam tree parts with different adhesive percentages. The research uses a completely randomized factorial design, with factors including tree parts (trunk, branches, twigs) and tapioca adhesive percentages (7.5%, 10%, 12.5%), followed by a Least Significant Difference (LSD) test. The results show that the tree part has no significant effect on moisture content, compressive strength, ash content, volatile matter, fixed carbon, or calorific value. However, the tree part significantly affects the density. The adhesive percentage has no significant effect on density and calorific value but significantly affects moisture content, compressive strength, ash content, volatile matter, and fixed carbon. The interaction between treatments has no significant effect on any pellet test parameters. The wood pellets show average values for the treatment interaction that meet the SNI 8021-2014 standards, except for moisture content.